2017
DOI: 10.1002/joc.5338
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China

Abstract: Location of the dune fields in northern China, and the topographic features they are associated with.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
(208 reference statements)
4
9
0
Order By: Relevance
“…The PDF in six subregions showed a similar distribution, while the fraction of high SWS is higher in northeastern and northern China. Over China, the 95th percentile corresponded to 5 m s 21 , which has been used as a threshold for dust emissions (Cui et al 2018) and has been used in many extreme climate studies (Xu et al 2006). Therefore, we chose the 95th percentile of daily mean SWS as a reference to define strong wind.…”
Section: F Trend Analysismentioning
confidence: 99%
“…The PDF in six subregions showed a similar distribution, while the fraction of high SWS is higher in northeastern and northern China. Over China, the 95th percentile corresponded to 5 m s 21 , which has been used as a threshold for dust emissions (Cui et al 2018) and has been used in many extreme climate studies (Xu et al 2006). Therefore, we chose the 95th percentile of daily mean SWS as a reference to define strong wind.…”
Section: F Trend Analysismentioning
confidence: 99%
“…However, long-term climatic data may be subject to inhomogeneities resulting from artificial changes in instruments and observing environment, which will result in uncertainty in the assessment of climate trends (Azorin-Molina et al, 2014;Cui et al, 2017). To further test the credibility of wind speed data series, we adopted the standard normal homogeneity test (SNHT) method (Alexandersson, 1986), which has been widely used in detecting inhomogeneities and breakpoints in climate series (Liu, 2000;Wu et al, 2018a).…”
Section: Quality Control and Homogeneity Testmentioning
confidence: 99%
“…Sand drift potential is a good index to assess the intensity of aeolian activity, as this variable represents the wind's potential ability to transport sediment; as a result, it has been widely used in aeolian research. Cui et al (2017) discussed the spatiotemporal variation of the wind energy environment in the dune fields of northern China, and provided a reference for regional desertification control. showed that drift potential was closely related to the migration rate of sand dunes, and was an important parameter that reflected the intensity of aeolian activity.…”
Section: Introductionmentioning
confidence: 99%
“…The wind regime data was provided by the Chinese National Meteorological Information Centre (http://data.cma.cn). These data passed strict quality control standards (Cui et al, 2018). The drift potential is calculated as follows:…”
Section: Wind Regimesmentioning
confidence: 99%